Study on the Physiological Function of a - Tocopherol, Vitamin (E) on Lipoproteins Levels in Serum of Apparantly Healthy Individuals - Al-Masbhadani, Z.I.; Al-Zubadyi, L.S.; AI- Baityi, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The role of free radicals generation and Lipid Peroxidation during the course of ischemic heart disease is well establshed as a basic for Pthogenesis and subsequent tissue damage consequenes . In an attempt to shed a light on the possible relationship between lipid peroxidation and some antioxidant. The effect of vitamine E (as a potent antioxidant free radical scavenger) . On the serum levels of the Lipoproteins, (HDLc) High Density Lipoprotein , (LDLc) Low Density Lipoprotein and (VLDLc) very Low Density Lipoprotein in healthy donors. The study includes (50) healthy donors from males and females , who had given Vitamin E (400 Ul) daily for one month and were divided into two groups. • Group (A): includes (25) males donors (20-40) years old, befor and after giving Vitamin E. • Group (B): includes (25) females donors (20-40) years , befor and after giving Vitamin E. The Level of Lipoproteins (HDLc), (LDLc), (VLDLc) and (LDLc)/ (HDLc)was determ ed in sera of healthy donors. The results of study indicated and confirmed the role of Vitamin (E) in reducing of (LDLc) Level, while an increase in (HDLc) level after Vitarnine (E) ingestion for the healthy donors .